Compensation of the Influence and Motivation of Work on Employee Performance with Job Satisfaction as a Mediating Variable in Ninja Xpress MSH Padang - Anwar, Saiful; Ikratullah, M. Insan (LPPM Universitas Bina Bangsa, 2023)
The purpose of this study was to examine the effect of compensation and work motivation variables on employee performance with job satisfaction as a mediating variable at Ninja Xpress MSH Padang. Collecting data by distributing questionnaires to 63 respondents using a saturated sampling technique, where all members of the population are sampled, using multiple linear regression testing with the help of the SPSS application. The results of the study show that compensation has a positive and significant effect on employee performance, work motivation has a positive and significant effect on employee performance, job satisfaction has a positive and significant effect on employee performance, compensation has a positive and significant effect on job satisfaction, work motivation has a positive and significant effect on employee performance. job satisfaction